Taking your iPod touch to the max - Grothaus, Michael (Technology in action series., 2011)
"Unleash your iPod touch and take it to the limit using secret tips and techniques. Fast and fun to read, Taking Your iPod touch 5 to the Max will help you get the most out of iOS 5 on your iPod touch. * You'll find all the best undocumented tricks, as well as the most efficient and enjoyable introduction to the iPod touch available. Starting with the basics, you'll quickly move on to discover the iPod touch's hidden potential, like how to connect to a TV and get contract-free VoIP. * From e-mail and surfing the Web, to using iTunes, iBooks, games, photos, ripping DVDs and getting free VoIP with Skype or FaceTime--whether you have a new iPod touch, or an older iPod touch with iOS 5, you'll find it all in this book. You'll even learn tips on where to get the best and cheapest iPod touch accessories. Get ready to take iPod touch to the max!"--Publisher's website